SIRT2-dependent CPT1A deacetylation in macrophages inhibits periodontitis - Jiang, Yixuan; Yao, Xiu; Jiang, Zhizhong; Liu, Xiaomeng; Sun, Boyuan; Guan, Zhengyu; Zhou, Lin; Li, Hongjiao (Frontiers in Pharmacology, 2025)
IntroductionPeriodontitis is intricately related to systemic disorders and exerts a negative impact on quality of life. Recent studies have suggested a potential association between periodontitis and fatty acid oxidation (FAO), a key metabolic process involved in energy production and cellular function. However, the molecular mechanisms underlying this relationship remain insufficiently understood. This study aims to explore the role of carnitine palmitoyltransferase 1A (CPT1A), a pivotal enzyme in fatty acid oxidation (FAO), in the pathogenesis of periodontitis.MethodsThe involvement of FAO in periodontitis was validated through bioinformatics analysis and quantitative real-time polymerase chain reaction (qRT-PCR). The anti-inflammatory effects of the CPT1A inhibitor Etomoxir (ETO) were assessed by qRT-PCR and Western blot analysis. The interaction between Sirtuin-2 (SIRT2) and CPT1A was confirmed via Chromatin Immunoprecipitation (ChIP)-qPCR. An experimental model of periodontitis was induced using silk ligation, and the effects of CPT1A inhibition on periodontitis were evaluated in mice treated with ETO. Micro-Computed Tomography (micro-CT) and histological analyses were employed to assess the impact of CPT1A inhibition on tissue architecture and inflammatory response in the periodontal tissues.ResultsETO reduced the expression levels of TNF-α, IL-6, IL-1β, NF-κB, and MAPK. Furthermore, it decreased cementoenamel junction-alveolar bone crest (CEJ-ABC) distance, immune cell infiltration in gingival tissues, and the expression levels of iNOS and p65. Additionally, ChIP-qPCR further confirmed the interaction between Sirtuin-2 (SIRT2)-CPT1A, thereby impacting the acetylation levels of CPT1A and decreasing CPT1A activity.ConclusionOverall, these findings demonstrate that SIRT2 binds to and deacetylates CPT1A, thereby inhibiting osteoclast differentiation and concurrently alleviating inflammation in periodontal tissues during experimental periodontitis progression.